Is it a Reliable Guide or a Source to be Approached with Caution? GenAI in Parents' Information Search Processes Regarding Their Children - Erol, Mustafa; Erol, Ahmet (SPRINGER, 2026)
Generative artificial intelligence (GenAI) is increasingly used by parents to get information on child care and learning. This study examines how parents use GenAI in their information-seeking process related to their children's care and learning. It looks at how this shapes decision-making and how parents emotionally interpret these experiences. Thirty parents of children aged 0-3 participated. Researchers collected data with open-ended qualitative questionnaires and analyzed it through inductive content analysis. Findings showed that parents used generative AI for quick information and guidance during periods of uncertainty, emergencies, or developmental questions. They viewed AI as a helpful resource for health, care, behavior, development, and planning activities. Parents did not always use AI suggestions directly; instead, they evaluated them by considering their experiences, their children's needs, and professional advice. Emotionally, some felt relief, a sense of security, or a sense of being in control, while others felt insecurity, anxiety, or caution.Conclusions: Parents view generative AI as a helpful, easy-to-access resource for child care and learning. They use it most when needing immediate answers or guidance. At the same time, they treat their information with caution by combining it with their own experiences and expert advice. Generative AI now works as a supporting tool for parents, not as a replacement for human judgment or expert help.
Keywords: Parents; Generative artificial intelligence; Children; AI-assisted parenting; Pediatrics